Invasion of Prosopis juliflora and its effects on soil physicochemical properties in Afar region, Northeast Ethiopia - Shiferaw, W.; Demissew, S.; Bekele, T.; Aynekulu, E.; Pitroff, W. (Elsevier, 2021)
Woody species within pastures and savannas are often associated with ‘resource islands’ characterized by higher fertility under canopies trees. The aims of this study were to evaluate (1) the effects of Prosopis juliflora on some soil physicochemical properties and (2) the impacts of Prosopis invasion on soil salinity. For soil physicochemical analysis, a total of 104 soil samples from Teru and Yalo Districts were collected. The soil samples were collected from soil depths of 0e15 cm and 15e30 cm in Prosopis invaded and non invaded open grazing lands. Invasion of Prosopis had significantly affected soil pH, exchangeable Naþ, water soluble Ca2þ þ Mg2þ, water soluble Naþ, and exchangeable sodium percentage in Teru and Yalo Districts (p < 0.05). The invasion of Prosopis significantly increased soil pH (1.5%), but decreased exchangeable Naþ (24.2%), exchangeable sodium percentage (21.6%), and water soluble Ca2þ þ Mg2þ (39.9%) than non-invaded lands. Clay content of Prosopis invaded lands was higher by 19% than non invaded lands. However, sand content of soil was higher under non-invaded lands by 5.6% than Proso pis invaded lands. Most results indicated that invasion of Prosopis had positive effects on physicochemical properties and thus conducive for cereal crops and forages.